2021
DOI: 10.3390/s21227463
|View full text |Cite
|
Sign up to set email alerts
|

EGM Toolbox—Interface for Controlling ABB Robots in Simulink

Abstract: The development of industrial robotics requires the use of increasingly sophisticated control algorithms. In modern tasks posed by industry, it is not sufficient for the manipulator to move along a programmed path, reaching individual points with the greatest accuracy. There is a need for solutions that can allow detection and avoidance of obstacles appearing on the robot’s path and that can compensate the path for low-repetitive workpieces, adjust the strength of the impact of manipulator tools on the workpie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The presented method was developed for the use in robotic machining of elements with imprecise shape, e.g., thin-walled castings or parts made of plastics, which have low precision and are very flexible. The difficulty in its application in practice is the need to modify standard industrial robot controllers [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presented method was developed for the use in robotic machining of elements with imprecise shape, e.g., thin-walled castings or parts made of plastics, which have low precision and are very flexible. The difficulty in its application in practice is the need to modify standard industrial robot controllers [44].…”
Section: Discussionmentioning
confidence: 99%
“…It follows that 𝑉 ̇ is negative outside the compact sets defined by Eqs ( 41)- (44). According to the extension of the standard Lyapunov theory, it can be concluded that ‖𝑠 𝜏 ‖, |𝑠 𝑛𝑖 |, ‖𝑊 ̃𝜏‖ 𝐹 and ‖𝑊 ̃𝑛𝑖 ‖ 𝐹 are uniformly ultimately bounded, and the control system is stable.…”
Section: Neural Position/force Tracking Controlmentioning
confidence: 98%
“…These results become particularly important for extending the use of IRs to large-scale machining operations. To this aim, promising results have also been obtained by means of force-based compensations, as documented in [45][46][47]. In general, the adoption of force/torque sensors directly mounted on the robot's end-effector has been extended to many fields, ranging from automatic part handling to the execution of collaborative tasks (e.g., operator hand-guiding as depicted in Figure 4 and described in [48,49]).…”
Section: External Trajectory Generatormentioning
confidence: 99%
“…The off-line programming method consists of generating robot paths with the use of a virtual environment [3,4]. CAD models of individual robots, auxiliary devices, such as feeders, tool changers, part warehouses, etc., are imported into the environment.…”
Section: Off-line Programmingmentioning
confidence: 99%